Immunogenicity, safety, and tolerability of a recombinant measles-vectored Lassa fever vaccine: a randomised, placebo-controlled, first-in-human trial. Issue 10384 (15th April 2023) - Tschismarov, Roland; Van Damme, Pierre; Germain, Clara; De Coster, Ilse; Mateo, Mathieu; Reynard, Stephanie; Journeaux, Alexandra; Tomberger, Yvonne; Withanage, Kanchanamala; Haslwanter, Denise; Terler, Katherine; Schrauf, Sabrina; et al.
Summary: Background: Lassa fever is a substantial health burden in west Africa. We evaluated the safety, tolerability, and immunogenicity of a recombinant, live-attenuated, measles-vectored Lassa fever vaccine candidate (MV-LASV). Methods: This first-in-human phase 1 trial—consisting of an open-label dose-escalation stage and an observer-blinded, randomised, placebo-controlled treatment stage—was conducted at a single site at the University of Antwerp, Antwerp, Belgium, and involved healthy adults aged 18–55 years. Participants in the dose-escalation stage were sequentially assigned to a low-dose group (two intramuscular doses of MV-LASV at 2 × 10 4 times the median tissue culture infectious dose) or a high-dose group (two doses at 1 × 10 5 times the median tissue culture infectious dose). Participants in the double-blinded treatment stage were randomly assigned in a 2:2:1 ratio to receive low dose, high dose, or placebo. The primary endpoint was the rate of solicited and unsolicited adverse events up to study day 56 and was assessed in all participants who received at least one dose of investigational product. The trial is registered with ClinicalTrials.gov, NCT04055454, and the European Union Drug Regulating Authorities Clinical Trials Database, 2018-003647-40, and is complete. Findings: Between Sept 26, 2019, and Jan 20, 2020, 60 participants were enrolled and assigned to receive placebo (n=12) or MV-LASV (n=48). All 60 participants received at least one study treatment. Most adverse events occurred during the treatment phase, and frequencies of total solicited or unsolicited adverse events were similar between treatment groups, with 96% of participants in the low-dose group, 100% of those in the high-dose group, and 92% of those in the placebo group having any solicited adverse event (p=0·6751) and 76% of those in the low-dose group, 70% of those in the high-dose group, and 100% of those in the placebo group having any unsolicited adverse event (p=0·1047). The only significant difference related to local solicited adverse events, with higher frequencies observed in groups receiving MV-LASV (24 [96%] of 25 participants in the low-dose group; all 23 [100%] participants in the high-dose group) than in the placebo group (6 [50%] of 12 participants; p=0·0001, Fisher-Freeman-Halton test). Adverse events were mostly of mild or moderate severity, and no serious adverse events were observed. MV-LASV also induced substantial concentrations of LASV-specific IgG (geometric mean titre 62·9 EU/ml in the low-dose group and 145·9 EU/ml in the high-dose group on day 42). Interpretation: MV-LASV showed an acceptable safety and tolerability profile, and immunogenicity seemed to be unaffected by pre-existing immunity against the vector. MV-LASV is therefore a promising candidate for further development. Funding: Coalition for Epidemic Preparedness Innovations.